Bacteriological Profile of Surgical Site Infection Following Gastrointestinal Surgery and Their Antibiogram - Shrestha, Neha; Sharma, Sangita; Ghimire, Bikal; Prasad, Pravin; Das, Debashis; Sherchand, Jeevan Bahadur (Journal of Nepal Health Research Council, 2023)
Background: Surgical site infection is one of the common complication following abdominal surgery. It causes great morbidity and mortality, further increasing prevalence of multidrug resistant bacteria have made its management very challenging. The current study aims to identify causative agent responsible for surgical site infection and their antibiotic resistance patterns. Methods: This study was conducted among patients developing surgical site infection following gastrointestinal surgery in Tribhuvan university teaching hospital over a period of one year. The samples were collected and processed according to standard methods. The bacterial pathogens with their antimicrobial susceptibility were determined and resistant pattern like methicillin resistant Staphylococcus aureus and extended spectrum beta lactamase were further detected. Results: A total of 832 patients had under gone gastrointestinal surgery during the study period. Among them, 162 cases (19.5%) developed surgical site infection and 125 cases showed growth in culture. A total of 160 aerobic bacteria were isolated; Escherichia coli (29.9%) was the commonest organism with 40.8% being extended spectrum beta lactamase producer and 47.4% of Staphylococcus aureus were methicillin resistant. About 75.9% (85/112) of gram negative bacteria and 60.4% (29/48) gram positive bacteria were multi drug resistant. Conclusions: The burden of multi drug resistant bacteria causing surgical site infection is high which needs to be addressed timely. Good surveillance of bacterial antibiogram and rational antimicrobial use is necessary to reduce emergence and spread of resistant bacteria. Keywords: Extended Spectrum beta lactamase; gastrointestinal surgery; methicillin resistant staphylococcus aureus; multi drug resistance; surgical site infection